RESPONSE TO APPLYING COW DUNG BOKASHI FERTILIZER AND LIQUID ORGANIC FERTILIZER HOUSEHOLD WASTE TOWARD GROWTH AND PRODUCTION CUCUMBER PLANTS (Cucumi sativus L.) - Yudi Siswanto; Annisa Anggreini Siswanto (Journal of Engineering, Electrical and Informatics, 2022)
Cucumber (Cucumis sativus L.) has a very high economic value because cucumbers are widely consumed by people, so the need for cucumbers continues to increase every year. The nutritional value of cucumbers is quite good because this vegetable or fruit is a source of minerals and vitamins. The purpose of the study was to determine the application of cow dung bokashi fertilizer and liquid organic fertilizer for household waste and its interaction with the growth and production of cucumber plants. This research method uses a Factorial Randomized Group Design (RAK), which consists of 2 (two) factors. The first factor is the application of cow dung bokashi fertilizer which is divided into 4 levels, namely S0 = 0.00 kg/plot (control), S1 = 2.16 kg/plot S2 = 4.32 kg/plot, and S3 = 6.48 kg/plot. The second factor is that liquid organic fertilizer household waste is divided into 4 levels, namely L0 = 0 cc/liter of water/plant (control), L1 = 100 cc/plant, L2 = 200 cc/plant, and L3 = 300 cc/plant. The parameters observed are plant length (cm), number of fruits per sample (fruit), number of fruits per plot (fruit), fruit diameter (cm), fruit length per plot (cm), fruit weight per sample (grams) and fruit weight per plot (grams). From the results of statistical analysis, it shows that the application of cow dung bokashi fertilizer and liquid organic fertilizer from household waste does not affect plant length (cm), but has an influence on the number of fruits per sample (fruit), the number of fruits per plot (fruit), the diameter of the fruit (cm), the length of the fruit per plot (cm) the weight of the fruit per sample (grams, and the weight of the fruit per plot (grams). The interaction of the treatment of applying organic fertilizer bokashi cow dung and liquid organic fertilizer household waste has no effect on plant length (cm), number of fruits per sample (fruit), number of fruits per plot (fruit), fruit diameter (cm), fruit length per plot (cm), fruit weight per sample (grams) and fruit weight per plot (grams)